2005
DOI: 10.1029/2005jg000013
|View full text |Cite
|
Sign up to set email alerts
|

Changing snow and shrub conditions affect albedo with global implications

Abstract: [1] Observations suggest that shrub abundance in the Arctic is increasing owing to climate warming. We investigated the ramifications of a tundra-to-shrubland transition on winter energy exchange. At five sites in Alaska we suspended a 50-m-long cable above the vegetation and from this measured how the vegetation interacted with the snow and affected albedo. The sites defined a gradient from nearly shrub-free tundra to a woodland with a continuous shrub canopy. Where the shrubs were small, thin-stemmed, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
320
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(338 citation statements)
references
References 47 publications
15
320
0
1
Order By: Relevance
“…Another important process that contributes to the snowmelt variability in Arctic basins is the difference in melt rates introduced by the shrub canopy in shrub tundra areas compared to open tundra areas that have only a short vegetation cover (Liston et al, 2002;Marsh et al, 2003;Sturm et al, 2005). Figure 9 illustrates the difference in SWE between the simulated shrub tundra and simulated open tundra areas for the duration of the model runs.…”
Section: Atmosphere-oceanmentioning
confidence: 99%
“…Another important process that contributes to the snowmelt variability in Arctic basins is the difference in melt rates introduced by the shrub canopy in shrub tundra areas compared to open tundra areas that have only a short vegetation cover (Liston et al, 2002;Marsh et al, 2003;Sturm et al, 2005). Figure 9 illustrates the difference in SWE between the simulated shrub tundra and simulated open tundra areas for the duration of the model runs.…”
Section: Atmosphere-oceanmentioning
confidence: 99%
“…Heat transport in snow is largely dependent on the microstructure of the snow (pore and grain distribution and size) which is difficult to quantify (Sturm et al, 1997), particularly for continental-scale simulations. The thermal conductivity of snow is therefore often calculated using empirical functions that are based on measurable properties of snow.…”
Section: Snow Dynamicsmentioning
confidence: 99%
“…Anticipated changes in the vegetation as a result of warming air temperatures towards shrubbier vegetation could potentially provide more shading, change snowpack and alter heat flux into the soil as well (Sturm et al, 2005).…”
Section: Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern was reflected in the average air temperature of the two snowmelt periods which showed only small differences between 2013 and 2014 although the snowmelt period in 2014 was much longer compared to 2013. The combination of snow layer thickness, snow physical properties such as density or grain size (Warren, 1982), the fraction of exposed dark underlying surface and type of vegetation (Sturm and Douglas, 2005) controls the snow and soil surface albedo, with direct impact on R net . Our results showed that low and partly absent snow cover in the winter 2012/2013 resulted in a short snowmelt period dominated by low albedo of the snow-soil surface and increased average R net .…”
Section: Snow Cover and Surface Energy Budgetmentioning
confidence: 99%